A preparation method of synergistic antibacterial microcapsules and wood antibacterial anticorrosive coating
By using calcium alginate/polydopamine microcapsule shell material and phase change material core material, combined with the photothermal conversion performance activated by near-infrared light, the problems of high toxicity and poor anti-loss properties of existing wood antibacterial agents are solved, and low-cost and efficient photothermal-anti-bacterial agent synergistic antibacterial effect is achieved.
Patent Information
- Application Number
- CN202411796386.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-09
AI Technical Summary
Existing wood antibacterial agents have problems of high toxicity and poor loss resistance, and the preparation cost of photothermal-anti-anti-bacterial agent synergistic antibacterial materials is high, the process is complex, and it is difficult to produce on a large scale.
Calcium alginate/polydopamine is used as the shell material of the microcapsule, and the phase change material doped with antibacterial agent is used as the core material. The release of antibacterial agent is controlled through solid-liquid phase change of the phase change material, and the photothermal conversion performance of the microcapsule is activated by near-infrared light to achieve efficient synergistic antibacterial of photothermal-antibiotic agents.
It has achieved low-cost, simple process and large-scale production, good biocompatibility and long-term antibacterial and anti-molding effects, reducing its dependence on traditional antibacterial agents.
Smart Images

Figure CN119257111B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of coatings, and in particular to a preparation method of synergistic antibacterial microcapsules and a wood antibacterial and anticorrosive coating. Background Art
[0002] Wood is widely used in the fields of architecture, furniture, indoor and outdoor decoration, etc., because of its beautiful texture, color, rich source and renewable characteristics. However, wood itself is susceptible to biological invasions such as fungi and bacteria, and becomes moldy and breeds bacteria, thereby affecting its quality and service life. Traditional wood antibacterial agents such as 2-(thiocyanate methylmercapto)benzothiazole, methylene disulfate, octahydroxyquinoline copper, triazole compounds, thiophanate-methyl, etc., although they can play a good antibacterial effect, they have high toxicity, seriously endangering human health and environmental safety. In addition, the anti-loss property of the above-mentioned wood antibacterial agent cannot meet the needs of long-term preservation of wood, and particularly in a humid environment, its effect can significantly decrease, so it is necessary to further enhance its anti-loss property.
[0003] In recent years, the study of combining physical photothermal antibacterial with antibacterial agents for synergistic antibacterial has attracted widespread attention from many scholars. Photothermal antibacterial is a physical sterilization method that uses photothermal agents to convert light energy into heat, causing irreversible losses such as cell membrane rupture and protein denaturation at high temperatures. Studies have shown that combining photothermal antibacterial with antibacterial agents can achieve a synergistic antibacterial effect, thereby reducing dependence on antibacterial agents. Among them, the high temperature of photothermal will destroy the structural integrity of the biofilm, thereby promoting the penetration, destruction and diffusion of antibacterial agents into the biofilm. At the same time, the loss of antibacterial agents to bacterial membranes will lead to a decrease in the heat resistance of the cell membrane, further improving the photothermal sterilization efficiency. However, the existing photothermal-antibacterial agent synergistic antibacterial materials mostly rely on nanomaterials such as gold, silver, ZIF-8, and molybdenum disulfide as carriers. Their high cost and complex preparation process prevent them from being truly applied in practice. Therefore, it is necessary to develop a photothermal-antibacterial agent synergistic antibacterial agent that is low in cost, simple in preparation process, and can be mass-produced.
[0004] In addition, in order to solve the problem of antimicrobial agent loss, microencapsulation technology is used to effectively extend the life of the fungicide by encapsulating the antimicrobial agent in microcapsules and using microcapsule shell materials to delay its release. For example, in the prior art, essential oils are used as antimicrobial agents, which are encapsulated in polymelamine-formaldehyde microcapsules through in-situ polymerization and applied to water-based coatings. The prepared coatings show good antimicrobial effects. However, the polymelamine-formaldehyde shell materials used therein contain a large amount of formaldehyde and isocyanate, and their toxicity can cause damage to human health.
[0005] In summary, it is necessary to develop a photothermal-antibacterial agent controlled release synergistic antibacterial phase change microcapsule with low cost, simple preparation process and good biocompatibility. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a preparation method of synergistic antibacterial microcapsules and wood antibacterial and anticorrosive coatings. The synergistic antibacterial microcapsules prepared by the method of the present invention use calcium alginate / polydopamine as shell materials and phase change materials doped with antibacterial agents as core materials. The present invention uses the solid-liquid phase change of phase change materials to control the release of antibacterial agents, and the coating of calcium alginate / polydopamine shell materials can not only maintain the morphological stability of the phase change materials in a melted state, prevent the loss of phase change materials and antibacterial agents, but also give the microcapsules good photothermal conversion performance. By using near-infrared light as a switch, under continuous illumination, the temperature of the microcapsules is increased due to the photothermal conversion of the shell material, and after reaching the melting point of the core of the phase change material, the release of the antibacterial agent is triggered, thereby realizing efficient synergistic antibacterial of photothermal-antibacterial agents. After the synergistic antibacterial microcapsules of the present invention are made into coatings, they can be adsorbed on the surface of chitosan-modified wood by electrostatic action, have good binding properties, and can play a role in long-term antibacterial, mildew-proof and anticorrosive.
[0007] The specific technical scheme of the present invention is:
[0008] In a first aspect, the present invention provides a method for preparing a synergistic antibacterial microcapsule, comprising the following steps:
[0009] 1) Mix the melted phase change material and the antibacterial agent, cool them, and obtain the core material.
[0010] 2) Dissolve sodium alginate in isopropanol-water solution, add core material, heat to melt phase change material, add emulsifier hydrophobic nano calcium carbonate, and stir evenly.
[0011] 3) Add the acid solution dropwise to the product obtained in 2), and simultaneously add dopamine hydrochloride and a catalyst, and heat and stir.
[0012] 4) Pour the product obtained in 3) into water and filter to obtain synergistic antibacterial microcapsules with an average particle size of 30-100 microns.
[0013] The preparation principle of the present invention is: first, the antibacterial agent is added to the phase change material (such as paraffin) as the core material of the microcapsule, and then sodium alginate is dissolved in an isopropanol-water solution to provide sufficient alginate for the subsequent formation of calcium alginate. Then, the core material is used as the oil phase, and the sodium alginate-isopropanol-water solution is used as the water phase. After the phase change material is completely melted, hydrophobic nano-calcium carbonate is added as an emulsifier to prepare an oil-in-water emulsion. In this process, since the hydrophobic nano-calcium carbonate tends to be dispersed inside the oil phase, the present invention changes the polarity of the water phase by adding isopropanol, which can promote the migration of hydrophobic nano-calcium carbonate to the oil-water interface, improve the emulsification effect, and further effectively regulate the morphology of the microcapsule. After a stable emulsion is formed by continuous heating and stirring, an acid solution is added to dissolve the calcium carbonate on the water phase side to release calcium ions, which react with alginate to form calcium alginate through the interface on the surface of the phase change material droplet. Dopamine hydrochloride and a catalyst are added at the same time. Under the catalysis of the catalyst, dopamine hydrochloride oxidizes and self-polymerizes to generate polydopamine, and finally obtains synergistic antibacterial microcapsules. Polydopamine can not only give the microcapsules excellent light-to-heat conversion performance, but also form a cross-linked network with calcium alginate, further improving the strength of the microcapsule shell material.
[0014] The synergistic antibacterial microcapsules prepared by the present invention use calcium alginate / polydopamine as shell materials and phase change materials doped with antibacterial agents as core materials. In the above-mentioned preparation process, the present invention incorporates the antibacterial agent into the phase change material, and uses the solid-liquid phase change of the phase change material to control the release of the antibacterial agent. The coating of the calcium alginate / polydopamine shell material can not only maintain the morphological stability of the phase change material in the melted state, prevent the loss of the phase change material and the antibacterial agent, but also give the microcapsules good photothermal conversion performance. By using near-infrared light as a switch, under continuous illumination, the temperature of the microcapsules rises due to the photothermal conversion of the shell material, and after reaching the melting point of the core of the phase change material, the release of the antibacterial agent is triggered, thereby realizing efficient synergistic antibacterial of photothermal-antibacterial agent.
[0015] Preferably, in 2), the concentration of the isopropanol-water solution is 5-15wt%.
[0016] The present invention finds that the concentration of isopropanol in the isopropanol-water solution has an important influence on regulating the polarity of the dispersion medium and regulating the distribution of hydrophobic nano-calcium carbonate, thereby significantly affecting the morphology and particle size of the microcapsules. Specifically: when isopropanol is not added, a large number of irregularly shaped antibacterial microcapsules will eventually be obtained, and have a large average particle size and particle size distribution (>150μm), which is because the hydrophobic nano-calcium carbonate tends to be dispersed in the oil phase, resulting in poor emulsification ability. When the concentration of isopropanol is about 5-15wt%, the antibacterial phase change microcapsules formed are uniformly spherical, and the particle size is significantly reduced (30-100μm) compared with no isopropanol added. This is because the addition of isopropanol reduces the polarity of the dispersed phase, causing the hydrophobic nano-calcium carbonate to tend to disperse at the oil-water interface, reducing the surface tension of the emulsion droplets, thereby reducing the particle size of the microcapsules. However, when the concentration of isopropanol was increased to 20%, a large number of flocs with a diameter of 0.2-1 mm were generated, and a large number of phase change material particles were observed in the formed flocs. When the concentration of isopropanol was further increased to 30%, only a small amount of phase change material was encapsulated in the microcapsules. Therefore, when the concentration of isopropanol-water solution was 5-15wt%, antibacterial microcapsules with the best morphology and particle size could be obtained.
[0017] Preferably, in 2), the solid-to-liquid ratio of sodium alginate to isopropanol-water solution is 1.5-3 g / 100 mL.
[0018] The present invention finds that the amount of sodium alginate used also has a significant effect on the morphology and particle size of the microcapsules. Specifically: if the amount of sodium alginate used is too little, irregular calcium alginate / polydopamine aggregates will eventually be formed, and a large number of paraffin particles will be coated therein. The reason is that at low concentrations of sodium alginate, the calcium ions released after the calcium carbonate is dissolved can further diffuse, causing a large number of calcium alginate / polydopamine microspheres that wrap the phase change material particles to aggregate, eventually forming large-sized aggregates. As the amount of sodium alginate used increases, the number and size of the calcium alginate / polydopamine aggregates gradually decrease.
[0019] Preferably, in 2), the solid-to-liquid ratio of the hydrophobic nano-calcium carbonate to the isopropanol-water solution is 0.8-1 g / 100 mL.
[0020] The present invention finds that the amount of hydrophobic nano-calcium carbonate used also significantly affects the morphology and particle size of the microcapsules. Specifically: if the amount of hydrophobic nano-calcium carbonate used is too little, it is found that only a small amount of irregular calcium alginate / polydopamine aggregates are formed. The reason is that too little calcium carbonate cannot form a stable emulsion and provide enough calcium ions. As the amount of hydrophobic nano-calcium carbonate used increases, the particle size of the obtained microcapsules gradually decreases. However, when the amount of hydrophobic nano-calcium carbonate used is too much, the number of microcapsules formed will be significantly reduced.
[0021] Preferably, in 1), the mass ratio of the phase change material to the antibacterial agent is (2500-7500):(5-15).
[0022] Preferably, in 1), the phase change material is paraffin with a melting point of 48-50°C.
[0023] Preferably, in 1), the antibacterial agent is amoxicillin.
[0024] Preferably, in 2), the solid-to-liquid ratio of the core material to the isopropanol-water solution is 4-6 g / 100 mL.
[0025] Preferably, in 2), the hydrophobic nano calcium carbonate is XFI11 type produced by Xianfeng Nanotechnology Co., Ltd.
[0026] Preferably, in 2), the heating and melting temperature is 55-65°C; the stirring speed is 500-1000 rpm, and the stirring time is 1-5h.
[0027] Preferably, in 3), the acid solution is an aqueous acetic acid solution with a concentration of 0.5-1.5 M; the volume ratio of the acid solution to the isopropanol-water solution in 2) is (5-15):100.
[0028] Preferably, in 3), the solid-to-liquid ratio of the dopamine hydrochloride to the isopropanol-water solution in 2) is 0.08-0.12 g / 100 mL.
[0029] Preferably, in 3), the catalyst is ammonium persulfate.
[0030] Preferably, in 3), the solid-to-liquid ratio of the catalyst to the isopropanol-water solution in 2) is 0.04-0.06 g / 100 mL.
[0031] Preferably, in 3), the heating and stirring temperature is 55-65° C., the stirring speed is 200-600 rpm, and the time is 1-5 h.
[0032] In a second aspect, the present invention provides an antibacterial and anticorrosive coating for wood, comprising independent components a and b, wherein component a is a chitosan solution for pre-soaking wood, and component b is a solution containing the synergistic antibacterial microcapsules obtained by the above preparation method for post-soaking wood.
[0033] The present invention uses layer-by-layer self-assembly technology to construct a coating on the wood surface. Since the wood surface contains abundant hydroxyl and carboxyl groups, it carries a large amount of negative charge. In the solution, cationic chitosan can be adsorbed to the wood surface by electrostatic action, making the surface positively charged. Since the shell material of the antibacterial phase-change microcapsule contains a large amount of alginate, the surface of the microcapsule carries a negative charge. Therefore, the antibacterial phase-change microcapsule is fixed on the wood surface impregnated with chitosan by electrostatic adsorption.
[0034] Preferably, the content of chitosan in component a is 1-3wt%; the content of synergistic antibacterial microcapsules in component b is 1-3wt%.
[0035] Preferably, the pre-immersion time of the wood in component a is 60-120 min; and the post-immersion time of the wood in component b is 60-120 min.
[0036] Compared with the prior art, the beneficial effects of the present invention are:
[0037] (1) The present invention cleverly combines photothermal antibacterial and antibacterial agent antibacterial with phase change microcapsules, achieving synergistic antibacterial of photothermal-antibacterial agent controlled release. The present invention utilizes the solid-liquid phase change of phase change materials to control the release of antibacterial agents, and the coating of calcium alginate / polydopamine shell material can not only maintain the morphological stability of the phase change material in the melted state, prevent the loss of phase change materials and antibacterial agents, but also give the microcapsules good photothermal conversion performance. By using near-infrared light as a switch, under continuous illumination, the temperature of the microcapsules rises due to the photothermal conversion of the shell material. After reaching the melting point of the core of the phase change material, the release of the antibacterial agent is triggered, thereby achieving efficient synergistic antibacterial of photothermal-antibacterial agents.
[0038] (2) After the synergistic antibacterial microcapsules of the present invention are made into coatings, they can be adsorbed on the surface of chitosan-modified wood through electrostatic action, have good binding properties, and can play a long-term antibacterial, anti-mildew and anti-corrosion role. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a diagram of the preparation mechanism of the synergistic antibacterial microcapsules (i.e., calcium alginate / polydopamine antibacterial phase change microcapsules) of the present invention.
[0040] Figure 2 The present invention is a flow chart for preparing the antibacterial and anticorrosive coated wood.
[0041] Figure 3 This is the SEM image of hydrophobic nano-calcium carbonate.
[0042] Figure 4 These are digital photos of hydrophobic nano-calcium carbonate dispersed in isopropanol-water solutions of different concentrations after adding 1 mL of dichloromethane.
[0043] Figure 5Schematic diagram of the effect of isopropanol concentration on the distribution of hydrophobic nano-calcium carbonate at the oil-water interface.
[0044] Figure 6 This is a metallographic microscope image of the calcium alginate / polydopamine antibacterial phase change microcapsules in Example 1.
[0045] Figure 7 This is a metallographic microscope image of the calcium alginate / polydopamine antibacterial phase change microcapsules in Example 2.
[0046] Figure 8 This is a metallographic microscope image of the calcium alginate / polydopamine antibacterial phase change microcapsules in Example 3.
[0047] Fig. 9 This is a metallographic microscope image of the calcium alginate / polydopamine antibacterial phase change microcapsules in Example 4.
[0048] Fig.10 This is a metallographic microscope image of the calcium alginate / polydopamine antibacterial phase change microcapsules in Example 5.
[0049] Fig.11 This is a metallographic microscope image of the calcium alginate / polydopamine antibacterial phase change microcapsules in Example 6.
[0050] Fig.12 This is a metallographic microscope image of the calcium alginate / polydopamine antibacterial phase change microcapsules in Example 7.
[0051] Fig.13 This is a metallographic microscope image of the calcium alginate / polydopamine antibacterial phase change microcapsules in Example 8.
[0052] Fig.14 This is a metallographic microscope image of the calcium alginate / polydopamine antibacterial phase change microcapsules in Example 9.
[0053] Fig.15 This is a metallographic microscope image of the calcium alginate / polydopamine antibacterial phase change microcapsules in Example 10.
[0054] Fig.16 This is a metallographic microscope image of the calcium alginate / polydopamine antibacterial phase change microcapsules in Example 11.
[0055] Fig.17 This is a metallographic microscope image of the calcium alginate / polydopamine antibacterial phase change microcapsules in Example 12.
[0056] Fig.18 This is the SEM image of the calcium alginate / polydopamine antibacterial phase change microcapsules in Example 11.
[0057] Fig.19 This is the FTIR graph of calcium alginate / polydopamine antibacterial phase change microcapsules in Example 11.
[0058] Fig. 20 The DSC graphs of paraffin wax and calcium alginate / polydopamine antibacterial phase change microcapsules in some examples are shown.
[0059] Fig.21 The photothermal curves of calcium alginate / polydopamine antibacterial phase change microcapsules, pure calcium alginate phase change microcapsules and calcium alginate / polydopamine gel in Example 11 are shown. DETAILED DESCRIPTION
[0060] The present invention will be further described below in conjunction with the embodiments.
[0061] In a first aspect, a method for preparing a synergistic antibacterial microcapsule comprises the following steps:
[0062] 1) Mix the melted phase change material and the antibacterial agent, cool them, and obtain the core material.
[0063] Preferably, the mass ratio of the phase change material to the antibacterial agent is (2500-7500):(5-15). The phase change material is paraffin with a melting point of 48-50° C. The antibacterial agent is amoxicillin.
[0064] 2) Dissolve sodium alginate in 5-15wt% isopropanol-water solution, add core material, heat to melt phase change material, add emulsifier hydrophobic nano calcium carbonate, and stir evenly. The solid-liquid ratio of sodium alginate to isopropanol-water solution is 1.5-3g / 100mL; the solid-liquid ratio of hydrophobic nano calcium carbonate to isopropanol-water solution is 0.8-1g / 100mL.
[0065] Preferably, the solid-liquid ratio of the core material to the isopropanol-water solution is 4-6 g / 100 mL. The hydrophobic nano calcium carbonate is XFI11 type from Xianfeng Nano. The heating and melting temperature is 55-65° C.; the stirring speed is 500-1000 rpm, and the stirring time is 1-5 h.
[0066] 3) Add the acid solution dropwise to the product obtained in 2), and simultaneously add dopamine hydrochloride and a catalyst, and heat and stir.
[0067] Preferably, the acid solution is an acetic acid aqueous solution with a concentration of 0.5-1.5M; the volume ratio of the acid solution to the isopropanol-water solution in 2) is (5-15):100. The solid-liquid ratio of dopamine hydrochloride to the isopropanol-water solution in 2) is 0.08-0.12g / 100mL. The catalyst is ammonium persulfate. The solid-liquid ratio of the catalyst to the isopropanol-water solution in 2) is 0.04-0.06g / 100mL. The temperature of the heating and stirring is 55-65°C, the stirring speed is 200-600rpm, and the time is 1-5h.
[0068] 4) Pour the product obtained in 3) into water and filter to obtain synergistic antibacterial microcapsules with an average particle size of 30-100 microns.
[0069] In the second aspect, a wood antibacterial and anticorrosive coating comprises independent components a and b, wherein component a is a chitosan solution for pre-soaking wood, and component b is a solution containing the synergistic antibacterial microcapsules obtained by the above preparation method for post-soaking wood.
[0070] Preferably, the content of chitosan in component a is 1-3wt%; the content of synergistic antibacterial microcapsules in component b is 1-3wt%.
[0071] Preferably, the pre-immersion time of the wood in component a is 60-120 min; and the post-immersion time of the wood in component b is 60-120 min. Specific embodiments
[0073] Example 1
[0074] Preparation of calcium alginate / polydopamine antibacterial phase change microcapsules (preparation mechanism as shown in Figure 1 shown):
[0075] 1. Melt 5g of paraffin with a melting point of 48-50℃ completely at 60℃, then add 10mg of amoxicillin antibacterial agent, and cool the paraffin after it is completely dissolved;
[0076] 2. Dissolve 2g of sodium alginate in 100mL of aqueous solution, then add 5g of paraffin containing antibacterial agent in step 1. Heat in a 60℃ water bath, and after the paraffin is completely melted, add 1g of hydrophobic nano calcium carbonate (XFI11 type from Xianfeng Nano Company), and continue to stir at 60℃ and 800rpm for 2h;
[0077] 3. Then, 10 mL of 1 M acetic acid solution was added to the three-necked flask at a rate of 1 mL / min, and 0.1 g of dopamine hydrochloride and 0.05 g of ammonium persulfate were added at the same time, and the mixture was stirred at 400 rpm at 60 °C for 2 h.
[0078] 4. After the reaction is completed, pour the solution in step 3 into 1 L of deionized water and filter it with filter paper to obtain calcium alginate / polydopamine antibacterial phase change microcapsules.
[0079] Preparation of antibacterial and anticorrosive coated wood (preparation process as shown in Figure 2 shown):
[0080] 1. Dry the cut wood at 60℃ for 1h;
[0081] 2. Soak the dried wood in a 1wt% chitosan solution for 90 min;
[0082] 3. The wood impregnated in step 2 was immersed again in a 1 wt% calcium alginate / polydopamine antibacterial phase change microcapsule solution for 90 min, then taken out and dried at 40° C. for 24 h to obtain an antibacterial and anticorrosive coated wood.
[0083] Example 2
[0084] Preparation of calcium alginate / polydopamine antibacterial phase change microcapsules:
[0085] 1. Melt 5g of paraffin with a melting point of 48-50℃ completely at 60℃, then add 10mg of amoxicillin antibacterial agent, and cool the paraffin after it is completely dissolved;
[0086] 2. Dissolve 2g of sodium alginate in 100mL of 10wt% isopropanol-water solution, then add 5g of paraffin containing antibacterial agent in step 1. Heat in a 60℃ water bath, add 1g of hydrophobic nano calcium carbonate (XFI11 type from Xianfeng Nano) after the paraffin is completely melted, and continue to stir at 60℃ and 800rpm for 2h;
[0087] 3. Then, 10 mL of 1 M acetic acid solution was added to the three-necked flask at a rate of 1 mL / min, and 0.1 g of dopamine hydrochloride and 0.05 g of ammonium persulfate were added at the same time, and the mixture was stirred at 400 rpm at 60 °C for 2 h.
[0088] 4. After the reaction is completed, pour the solution in step 3 into 1 L of deionized water and filter it with filter paper to obtain calcium alginate / polydopamine antibacterial phase change microcapsules.
[0089] Preparation of antimicrobial and anticorrosive coating for wood:
[0090] 1. Dry the cut wood at 60℃ for 1h;
[0091] 2. Soak the dried wood in a 1wt% chitosan solution for 90 min;
[0092] 3. The wood impregnated in step 2 was immersed again in a 1 wt% calcium alginate / polydopamine antibacterial phase change microcapsule solution for 90 min, then taken out and dried at 40° C. for 24 h to obtain an antibacterial and anticorrosive coated wood.
[0093] Example 3
[0094] Preparation of calcium alginate / polydopamine antibacterial phase change microcapsules:
[0095] 1. Melt 5g of paraffin with a melting point of 48-50℃ completely at 60℃, then add 10mg of amoxicillin antibacterial agent, and cool the paraffin after it is completely dissolved;
[0096] 2. Dissolve 2g of sodium alginate in 100mL of 20wt% isopropanol-water solution, then add 5g of paraffin containing antibacterial agent in step 1. Heat in a 60℃ water bath, add 1g of hydrophobic nano calcium carbonate (XFI11 type from Xianfeng Nano) after the paraffin is completely melted, and continue to stir at 60℃ and 800rpm for 2h;
[0097] 3. Then, 10 mL of 1 M acetic acid solution was added to the three-necked flask at a rate of 1 mL / min, and 0.1 g of dopamine hydrochloride and 0.05 g of ammonium persulfate were added at the same time, and the mixture was stirred at 400 rpm at 60 °C for 2 h.
[0098] 4. After the reaction is completed, pour the solution in step 3 into 1 L of deionized water and filter it with filter paper to obtain calcium alginate / polydopamine antibacterial phase change microcapsules.
[0099] Preparation of antimicrobial and anticorrosive coating for wood:
[0100] 1. Dry the cut wood at 60℃ for 1h;
[0101] 2. Soak the dried wood in a 1wt% chitosan solution for 90 min;
[0102] 3. The wood impregnated in step 2 was immersed again in a 1 wt% calcium alginate / polydopamine antibacterial phase change microcapsule solution for 90 min, then taken out and dried at 40° C. for 24 h to obtain an antibacterial and anticorrosive coated wood.
[0103] Example 4
[0104] Preparation of calcium alginate / polydopamine antibacterial phase change microcapsules:
[0105] 1. Melt 5g of paraffin with a melting point of 48-50℃ completely at 60℃, then add 10mg of amoxicillin antibacterial agent, and cool the paraffin after it is completely dissolved;
[0106] 2. Dissolve 2g of sodium alginate in 100mL of 30% isopropanol-water solution, then add 5g of paraffin containing antibacterial agent in step 1. Heat in a 60℃ water bath, add 1g of hydrophobic nano calcium carbonate (XFI11 type from Xianfeng Nano) after the paraffin is completely melted, and continue to stir at 800rpm at 60℃ for 2h;
[0107] 3. Then, 10 mL of 1 M acetic acid solution was added to the three-necked flask at a rate of 1 mL / min, and 0.1 g of dopamine hydrochloride and 0.05 g of ammonium persulfate were added at the same time, and the mixture was stirred at 400 rpm at 60 °C for 2 h.
[0108] 4. After the reaction is completed, pour the solution in step 3 into 1 L of deionized water and filter it with filter paper to obtain calcium alginate / polydopamine antibacterial phase change microcapsules.
[0109] Preparation of antimicrobial and anticorrosive coating for wood:
[0110] 1. Dry the cut wood at 60℃ for 1h;
[0111] 2. Soak the dried wood in a 1wt% chitosan solution for 90 min;
[0112] 3. The wood impregnated in step 2 was immersed again in a 1 wt% calcium alginate / polydopamine antibacterial phase change microcapsule solution for 90 min, then taken out and dried at 40° C. for 24 h to obtain an antibacterial and anticorrosive coated wood.
[0113] Example 5
[0114] Preparation of calcium alginate / polydopamine antibacterial phase change microcapsules:
[0115] 1. Melt 5g of paraffin with a melting point of 48-50℃ completely at 60℃, then add 10mg of amoxicillin antibacterial agent, and cool the paraffin after it is completely dissolved;
[0116] 2. Dissolve 0.5 g of sodium alginate in 100 mL of 10 wt% isopropanol-water solution, and then add 5 g of paraffin containing antibacterial agent in step 1. Heat in a 60°C water bath, and after the paraffin is completely melted, add 1 g of hydrophobic nano calcium carbonate (XFI11 type from Xianfeng Nano Company), and continue to stir at 60°C and 800 rpm for 2 h;
[0117] 3. Then, 10 mL of 1 M acetic acid solution was added to the three-necked flask at a rate of 1 mL / min, and 0.1 g of dopamine hydrochloride and 0.05 g of ammonium persulfate were added at the same time, and the mixture was stirred at 400 rpm at 60 °C for 2 h.
[0118] 4. After the reaction is completed, pour the solution in step 3 into 1 L of deionized water and filter it with filter paper to obtain calcium alginate / polydopamine antibacterial phase change microcapsules.
[0119] Preparation of antimicrobial and anticorrosive coating for wood:
[0120] 1. Dry the cut wood at 60℃ for 1h;
[0121] 2. Soak the dried wood in a 1wt% chitosan solution for 90 min;
[0122] 3. The wood impregnated in step 2 was immersed again in a 1 wt% calcium alginate / polydopamine antibacterial phase change microcapsule solution for 90 min, then taken out and dried at 40° C. for 24 h to obtain an antibacterial and anticorrosive coated wood.
[0123] Example 6
[0124] Preparation of calcium alginate / polydopamine antibacterial phase change microcapsules:
[0125] 1. Melt 5g of paraffin with a melting point of 48-50℃ completely at 60℃, then add 10mg of amoxicillin antibacterial agent, and cool the paraffin after it is completely dissolved;
[0126] 2. Dissolve 1g of sodium alginate in 100mL of 10wt% isopropanol-water solution, then add 5g of paraffin containing antibacterial agent in step 1. Heat in a 60℃ water bath, add 1g of hydrophobic nano calcium carbonate (XFI11 type from Xianfeng Nano) after the paraffin is completely melted, and continue to stir at 60℃ and 800rpm for 2h;
[0127] 3. Then, 10 mL of 1 M acetic acid solution was added to the three-necked flask at a rate of 1 mL / min, and 0.1 g of dopamine hydrochloride and 0.05 g of ammonium persulfate were added at the same time, and the mixture was stirred at 400 rpm at 60 °C for 2 h.
[0128] 4. After the reaction is completed, pour the solution in step 3 into 1 L of deionized water and filter it with filter paper to obtain calcium alginate / polydopamine antibacterial phase change microcapsules.
[0129] Preparation of antimicrobial and anticorrosive coating for wood:
[0130] 1. Dry the cut wood at 60℃ for 1h;
[0131] 2. Soak the dried wood in a 1wt% chitosan solution for 90 min;
[0132] 3. The wood impregnated in step 2 was immersed again in a 1 wt% calcium alginate / polydopamine antibacterial phase change microcapsule solution for 90 min, then taken out and dried at 40° C. for 24 h to obtain an antibacterial and anticorrosive coated wood.
[0133] Example 7
[0134] Preparation of calcium alginate / polydopamine antibacterial phase change microcapsules:
[0135] 1. Melt 5g of paraffin with a melting point of 48-50℃ completely at 60℃, then add 10mg of amoxicillin antibacterial agent, and cool the paraffin after it is completely dissolved;
[0136] 2. Dissolve 1.5g of sodium alginate in 100mL of 10wt% isopropanol-water solution, and then add 5g of paraffin containing antibacterial agent in step 1. Heat in a 60℃ water bath, and after the paraffin is completely melted, add 1g of hydrophobic nano calcium carbonate (XFI11 type from Xianfeng Nano Company), and continue to stir at 60℃ and 800rpm for 2h;
[0137] 3. Then, 10 mL of 1 M acetic acid solution was added to the three-necked flask at a rate of 1 mL / min, and 0.1 g of dopamine hydrochloride and 0.05 g of ammonium persulfate were added at the same time, and the mixture was stirred at 400 rpm at 60 °C for 2 h.
[0138] 4. After the reaction is completed, pour the solution in step 3 into 1 L of deionized water and filter it with filter paper to obtain calcium alginate / polydopamine antibacterial phase change microcapsules.
[0139] Preparation of antimicrobial and anticorrosive coating for wood:
[0140] 1. Dry the cut wood at 60℃ for 1h;
[0141] 2. Soak the dried wood in a 1wt% chitosan solution for 90 min;
[0142] 3. The wood impregnated in step 2 was immersed again in a 1 wt% calcium alginate / polydopamine antibacterial phase change microcapsule solution for 90 min, then taken out and dried at 40° C. for 24 h to obtain an antibacterial and anticorrosive coated wood.
[0143] Example 8
[0144] Preparation of calcium alginate / polydopamine antibacterial phase change microcapsules:
[0145] 1. Melt 5g of paraffin with a melting point of 48-50℃ completely at 60℃, then add 10mg of amoxicillin antibacterial agent, and cool the paraffin after it is completely dissolved;
[0146] 2. Dissolve 2.5g of sodium alginate in 100mL of 10wt% isopropanol-water solution, then add 5g of paraffin containing antibacterial agent in step 1. Heat in a 60℃ water bath, add 1g of hydrophobic nano calcium carbonate (XFI11 type from Xianfeng Nano) after the paraffin is completely melted, and continue to stir at 60℃ and 800rpm for 2h;
[0147] 3. Then, 10 mL of 1 M acetic acid solution was added to the three-necked flask at a rate of 1 mL / min, and 0.1 g of dopamine hydrochloride and 0.05 g of ammonium persulfate were added at the same time, and the mixture was stirred at 400 rpm at 60 °C for 2 h.
[0148] 4. After the reaction is completed, pour the solution in step 3 into 1 L of deionized water and filter it with filter paper to obtain calcium alginate / polydopamine antibacterial phase change microcapsules.
[0149] Preparation of antimicrobial and anticorrosive coating for wood:
[0150] 1. Dry the cut wood at 60℃ for 1h;
[0151] 2. Soak the dried wood in a 1wt% chitosan solution for 90 min;
[0152] 3. The wood impregnated in step 2 was immersed again in a 1 wt% calcium alginate / polydopamine antibacterial phase change microcapsule solution for 90 min, then taken out and dried at 40° C. for 24 h to obtain an antibacterial and anticorrosive coated wood.
[0153] Example 9
[0154] Preparation of calcium alginate / polydopamine antibacterial phase change microcapsules:
[0155] 1. Melt 5g of paraffin with a melting point of 48-50℃ completely at 60℃, then add 10mg of amoxicillin antibacterial agent, and cool the paraffin after it is completely dissolved;
[0156] 2. Dissolve 3g of sodium alginate in 100mL of 10wt% isopropanol-water solution, then add 5g of paraffin containing antibacterial agent in step 1. Heat in a 60℃ water bath, wait for the paraffin to completely melt, then add 1g of hydrophobic nano calcium carbonate (XFI11 type from Xianfeng Nano Company), and continue stirring at 60℃ and 800rpm for 2h;
[0157] 3. Then, 10 mL of 1 M acetic acid solution was added to the three-necked flask at a rate of 1 mL / min, and 0.1 g of dopamine hydrochloride and 0.05 g of ammonium persulfate were added at the same time, and the mixture was stirred at 400 rpm at 60 °C for 2 h.
[0158] 4. After the reaction is completed, pour the solution in step 3 into 1 L of deionized water and filter it with filter paper to obtain calcium alginate / polydopamine antibacterial phase change microcapsules.
[0159] Preparation of antimicrobial and anticorrosive coating for wood:
[0160] 1. Dry the cut wood at 60℃ for 1h;
[0161] 2. Soak the dried wood in a 1wt% chitosan solution for 90 min;
[0162] 3. The wood impregnated in step 2 was immersed again in a 1 wt% calcium alginate / polydopamine antibacterial phase change microcapsule solution for 90 min, then taken out and dried at 40° C. for 24 h to obtain an antibacterial and anticorrosive coated wood.
[0163] Example 10
[0164] Preparation of calcium alginate / polydopamine antibacterial phase change microcapsules:
[0165] 1. Melt 5g of paraffin with a melting point of 48-50℃ completely at 60℃, then add 10mg of amoxicillin antibacterial agent, and cool the paraffin after it is completely dissolved;
[0166] 2. Dissolve 2.5g of sodium alginate in 100mL of 10wt% isopropanol-water solution, then add 5g of paraffin containing antibacterial agent in step 1. Heat in a 60℃ water bath, add 0.6g of hydrophobic nano calcium carbonate (XFI11 type from Xianfeng Nano) after the paraffin is completely melted, and continue to stir at 800rpm for 2h at 60℃;
[0167] 3. Then, 10 mL of 1 M acetic acid solution was added to the three-necked flask at a rate of 1 mL / min, and 0.1 g of dopamine hydrochloride and 0.05 g of ammonium persulfate were added at the same time, and the mixture was stirred at 400 rpm at 60 °C for 2 h.
[0168] 4. After the reaction is completed, pour the solution in step 3 into 1 L of deionized water and filter it with filter paper to obtain calcium alginate / polydopamine antibacterial phase change microcapsules.
[0169] Preparation of antibacterial and anticorrosive coated wood: 1. Dry the cut wood at 60°C for 1 h;
[0170] 2. Soak the dried wood in a 1wt% chitosan solution for 90 min;
[0171] 3. The wood impregnated in step 2 was immersed again in a 1 wt% calcium alginate / polydopamine antibacterial phase change microcapsule solution for 90 min, then taken out and dried at 40° C. for 24 h to obtain an antibacterial and anticorrosive coated wood.
[0172] Embodiment 11
[0173] Preparation of calcium alginate / polydopamine antibacterial phase change microcapsules:
[0174] 1. Melt 5g of paraffin with a melting point of 48-50℃ completely at 60℃, then add 10mg of amoxicillin antibacterial agent, and cool the paraffin after it is completely dissolved;
[0175] 2. Dissolve 2.5g of sodium alginate in 100mL of 10wt% isopropanol-water solution, then add 5g of paraffin containing antibacterial agent in step 1. Heat in a 60℃ water bath, add 0.8g of hydrophobic nano calcium carbonate (XFI11 type from Xianfeng Nano) after the paraffin is completely melted, and continue to stir at 60℃ and 800rpm for 2h;
[0176] 3. Then, 10 mL of 1 M acetic acid solution was added to the three-necked flask at a rate of 1 mL / min, and 0.1 g of dopamine hydrochloride and 0.05 g of ammonium persulfate were added at the same time, and the mixture was stirred at 400 rpm at 60 °C for 2 h.
[0177] 4. After the reaction is completed, pour the solution in step 3 into 1 L of deionized water and filter it with filter paper to obtain calcium alginate / polydopamine antibacterial phase change microcapsules.
[0178] Preparation of antimicrobial and anticorrosive coating for wood:
[0179] 1. Dry the cut wood at 60℃ for 1h;
[0180] 2. Soak the dried wood in a 1wt% chitosan solution for 90 min;
[0181] 3. The wood impregnated in step 2 was immersed again in a 1 wt% calcium alginate / polydopamine antibacterial phase change microcapsule solution for 90 min, then taken out and dried at 40° C. for 24 h to obtain an antibacterial and anticorrosive coated wood.
[0182] Example 12
[0183] Preparation of calcium alginate / polydopamine antibacterial phase change microcapsules:
[0184] 1. Melt 5g of paraffin with a melting point of 48-50℃ completely at 60℃, then add 10mg of amoxicillin antibacterial agent, and cool the paraffin after it is completely dissolved;
[0185] 2. Dissolve 2.5g of sodium alginate in 100mL of 10wt% isopropanol-water solution, then add 5g of paraffin containing antibacterial agent in step 1. Heat in a 60℃ water bath, add 1.2g of hydrophobic nano calcium carbonate (XFI11 type from Xianfeng Nano) after the paraffin is completely melted, and continue to stir at 60℃ and 800rpm for 2h;
[0186] 3. Then, 10 mL of 1 M acetic acid solution was added to the three-necked flask at a rate of 1 mL / min, and 0.1 g of dopamine hydrochloride and 0.05 g of ammonium persulfate were added at the same time, and the mixture was stirred at 400 rpm at 60 °C for 2 h.
[0187] 4. After the reaction is completed, pour the solution in step 3 into 1 L of deionized water and filter it with filter paper to obtain calcium alginate / polydopamine antibacterial phase change microcapsules.
[0188] Preparation of antimicrobial and anticorrosive coating for wood:
[0189] 1. Dry the cut wood at 60℃ for 1h;
[0190] 2. Soak the dried wood in a 1wt% chitosan solution for 90 min;
[0191] 3. The wood impregnated in step 2 was immersed again in a 1 wt% calcium alginate / polydopamine antibacterial phase change microcapsule solution for 90 min, then taken out and dried at 40° C. for 24 h to obtain an antibacterial and anticorrosive coated wood.
[0192] Performance Testing and Characterization
[0193] Table 1 shows the preparation parameters of calcium alginate / polydopamine antibacterial phase change microcapsules in all embodiments:
[0194] Table 1
[0195]
[0196] Figure 3 The SEM image of the hydrophobic nano-calcium carbonate used in all the examples shows that the hydrophobic nano-calcium carbonate is in granular form, and its average particle size is 71 nm as measured by software. The Pickering emulsion prepared by nano-particles with small particle size has smaller emulsion droplets and higher stability.
[0197] Figure 4 The digital photos of the hydrophobic nano-calcium carbonate used in all the embodiments dispersed in the isopropanol-water solution of different concentrations after adding 1mL of dichloromethane. In the sample without adding isopropanol, the hydrophobic nano-calcium carbonate was completely dispersed in the dichloromethane, and only a small amount of hydrophobic nano-calcium carbonate was observed at the oil-water interface. After the addition of isopropanol, the formation of the cream layer can be clearly observed, and the thickness of the cream layer increases with the increase of the concentration of isopropanol. The above results show that the addition of isopropanol can effectively control the distribution of the hydrophobic nano-calcium carbonate by changing the polarity of the dispersion medium (such as Figure 5 As shown), the morphology of the synthesized calcium alginate / polydopamine antibacterial phase change microcapsules is controlled, and the calcium alginate / polydopamine antibacterial phase change microcapsules prepared with a 10% concentration of isopropanol-water solution have the best morphology.
[0198] Figure 6 , 7, 8, 9 (Examples 1, 2, 3, 4) are metallographic microscope photos of calcium alginate / polydopamine antibacterial phase change microcapsules prepared with isopropanol-water solutions of different concentrations. The prepared calcium alginate / polydopamine antibacterial phase change microcapsule dispersion was dropped on a glass slide and observed using a metallographic microscope. In Example 1, when isopropanol was not added, a large number of irregularly shaped calcium alginate / polydopamine antibacterial phase change microcapsules were formed, and had a large average particle size and particle size distribution of 176.42±72.24μm. This is because the hydrophobic nano-calcium carbonate tends to be dispersed in the oil phase, resulting in poor emulsification ability. In Example 2, when the concentration of isopropanol is 10%, the prepared calcium alginate / polydopamine antibacterial phase change microcapsules are uniformly spherical, and the particle size is significantly reduced compared with that without adding isopropanol, and the average particle size is 64.19±21.22μm. This is because the addition of isopropanol reduces the polarity of the dispersed phase, and makes the hydrophobic nano-calcium carbonate tend to be dispersed at the oil-water interface, and the surface tension of the emulsion droplets is reduced, thereby reducing the particle size of the microcapsules. In Example 3, when the concentration of isopropanol is increased to 20%, a large number of calcium alginate / polydopamine microspheres and calcium alginate / polydopamine flocs with a diameter of 0.2-1mm are generated. In addition, it can be observed that there are a large number of paraffin particles in the calcium alginate / polydopamine microspheres. In Example 4, when the concentration of isopropanol is further increased to 30%, only a small amount of paraffin particles are coated in the calcium alginate / polydopamine microspheres.
[0199] Fig.10 , 11, 12, 7, 13, 14 (Examples 5, 6, 7, 2, 8, 9) are metallographic microscope photos of calcium alginate / polydopamine antibacterial phase change microcapsules prepared with different amounts of sodium alginate. In Example 5, irregular calcium alginate / polydopamine aggregates were formed when the amount of sodium alginate was 0.5 g, and a large number of paraffin particles were coated therein. Different from the aggregates formed under 20% isopropanol concentration, only calcium alginate / polydopamine aggregates were generated when the amount of sodium alginate was 0.5 g, and no calcium alginate / polydopamine flocs were generated. The above results are due to the fact that the calcium alginate / polydopamine microspheres formed under 20% concentration of IPA are caused by the migration of hydrophobic nano-calcium carbonate to the aqueous phase, while the calcium alginate / polydopamine microspheres formed under 0.5g of sodium alginate are due to the fact that the calcium ions released after the dissolution of calcium carbonate can further diffuse under low concentrations of sodium alginate, so that a large number of calcium alginate / polydopamine microspheres wrapped with paraffin particles are agglomerated, and finally large-sized aggregates are formed. As the amount of sodium alginate increases, the number and size of calcium alginate / polydopamine aggregates gradually decrease. In Example 7, when the amount of sodium alginate is increased to 1.5g, the calcium alginate / polydopamine aggregates basically disappear, and are replaced by microcapsules of single paraffin particles coated with calcium alginate / polydopamine, and the average particle size is 64.59±20.84μm. In Example 8, as the amount of sodium alginate continued to increase to 2.5g, the number of calcium alginate / polydopamine antibacterial phase-change microcapsules formed increased and the average particle size decreased to 56.40±18.08μm. This is because the increase in the amount of sodium alginate increases the viscosity of the dispersed phase, which helps to reduce the average particle size and particle size distribution of the paraffin droplets. In Example 9, when the amount of sodium alginate was further increased to 3.0g, the average particle size of the calcium alginate / polydopamine antibacterial phase-change microcapsules decreased to 37.97±10.93μm.
[0200] Fig.15 , 16, 13, 17 (Examples 10, 11, 8, 12) are metallographic microscope photos of calcium alginate / polydopamine antibacterial phase-change microcapsules prepared with different amounts of hydrophobic nano-calcium carbonate. In Example 10, when the amount of hydrophobic nano-calcium carbonate was 0.6g, only a small amount of irregular calcium alginate / polydopamine aggregates were formed. This was because there was too little calcium carbonate to form a stable pickering emulsion and provide sufficient calcium ions. In Example 11, when the amount of hydrophobic nano-calcium carbonate was increased to 0.8g, a large number of calcium alginate / polydopamine antibacterial phase-change microcapsules with an average particle size of 52.04±16.12μm were formed. In Example 8, when the amount of hydrophobic nano-calcium carbonate was further increased to 1.0g, the average particle size of the formed calcium alginate / polydopamine antibacterial phase-change microcapsules increased slightly to 57.39±17.41μm. In Example 12, when the amount of hydrophobic nano-calcium carbonate continued to increase to 1.2 g, the number and average particle size of the formed calcium alginate / polydopamine antibacterial phase-change microcapsules were significantly reduced, and the particle size was about 31.70 ± 14.81 μm. In addition, it can be observed from the figure that the number of microcapsules formed at a higher calcium carbonate dosage was significantly reduced, and only a small amount of phase-change material was encapsulated into microcapsules.
[0201] Fig.18 This is a SEM image of the calcium alginate / polydopamine antibacterial phase-change microcapsules in Example 11. From the figure, it can be seen that most of the prepared microcapsules are spherical and have a smooth surface, with an average particle size of 52.27 μm, which is consistent with the particle size counted under a metallographic microscope.
[0202] Fig.19 The FTIR spectra of the paraffin wax and the calcium alginate / polydopamine antibacterial phase-change microcapsules prepared in Example 11 are shown in Table 1. In the FTIR spectrum of the paraffin wax, at 2958 cm -1 The absorption peak at 2916cm belongs to the asymmetric stretching vibration absorption peak of the CH bond. -1 and 2848cm -1 The absorption peak at 1463 cm is the stretching vibration peak of the CH bond. -1 The absorption peak at 719 cm is the bending vibration absorption peak of the CH bond. -1 The absorption peak at 3122cm is the in-plane swing vibration absorption peak of the CH bond. In the FTIR spectrum of calcium alginate / polydopamine antibacterial phase change microcapsules, in addition to the infrared characteristic peaks of paraffin mentioned above, -1 The broad absorption peak at 1580 cm is the stretching vibration absorption peak of OH and NH groups in alginate and polydopamine. -1 The broad absorption peak at is the CO2 in alginate - The asymmetric stretching vibration absorption peak of the group is at 1400cm -1The absorption peak at is the CO2 in alginate - The symmetric stretching vibration absorption peak of the group is at 1033 cm -1 The broad absorption peak at 876 cm is the asymmetric stretching vibration absorption peak of the COC bond in alginate. -1 The absorption peak at is the CO3 in the undissolved calcium carbonate 2- The out-of-plane bending vibration absorption peak of the group. The above structure shows that the prepared calcium alginate / polydopamine antibacterial phase change microcapsules have an ideal chemical composition.
[0203] Fig. 20 DSC graphs of paraffin wax and calcium alginate / polydopamine antibacterial phase-change microcapsules in Examples 2, 8, 9, and 11. DSC tests were performed on paraffin wax and Examples 2, 8, 9, and 11 with better morphology (smaller particle size and no agglomeration), and the phase change temperature and latent heat of the samples were analyzed based on the DSC spectra. The results are shown in Table 2. sm is the extrapolated onset temperature when heated to melt, T pm is the peak temperature, △H m is the melting enthalpy, T sf is the extrapolated starting temperature during cooling and solidification, T pf is the peak temperature, △H f is the solidification enthalpy. In addition, according to the formula:
[0204]
[0205] Calculate the encapsulation rate and encapsulation efficiency of the microcapsules, where △H m, PCM and △H f, PCM are the melting enthalpy and solidification enthalpy of paraffin, respectively, and △H m, MEPCM and △H f, MEPCM are the melting enthalpy and solidification enthalpy of the synthesized microcapsule samples, respectively, and the results are shown in Table 2. From the results, it can be seen that all embodiments have an encapsulation rate and encapsulation efficiency of more than 50%, and the encapsulation rate and encapsulation efficiency of embodiment 11 are the best.
[0206] Table 2
[0207]
[0208] Fig.21The photothermal curves of calcium alginate / polydopamine antibacterial phase change microcapsules, pure calcium alginate phase change microcapsules and calcium alginate / polydopamine gel in Example 11. After irradiation with 808nm laser for 10min and cooling for 20min, the thermal behavior of all sample dispersions was recorded. The temperature of the pure calcium alginate phase change microcapsule dispersion increased from 25°C to 30.5°C after irradiation for 10min, while the temperature of the calcium alginate / polydopamine antibacterial phase change microcapsule dispersion increased from 25°C to 56.9°C. The above results show that the addition of polydopamine gives the microcapsules good photothermal conversion ability. In addition, the temperature of the pure calcium alginate / polydopamine gel without paraffin rose rapidly to 63.6°C after irradiation for 10min. In comparison, the heating and cooling rates of the calcium alginate / polydopamine antibacterial phase change microcapsule dispersion are slower, because the phase change material can store and release latent heat during the heating and cooling process, thereby delaying the change in temperature.
[0209] Table 3 shows the plate count method inhibition rate of calcium alginate / polydopamine antibacterial phase change microcapsules modified wood in Example 11 under different conditions. The sample to be tested was placed in a culture dish containing bacterial solution, irradiated with near-infrared light for 10 minutes, and then cultured at 37°C for 30 minutes (the sample without near-infrared light treatment was also cultured at 37°C for 30 minutes), and then 100 μL of bacterial solution was taken to calculate the inhibition rate by coating the plate count, and the results are shown in Table 3. It can be seen from Table 3 that the number of bacteria in the sample without near-infrared light treatment has been reduced to a certain extent, which is attributed to the slight antibacterial activity of chitosan and polydopamine. After near-infrared light treatment, the inhibition rate was significantly improved, indicating that photothermal and antibiotics have a good synergistic antibacterial effect.
[0210] Table 3
[0211]
[0212] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0213] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a wood antiseptic and antibacterial coating containing synergistic antibacterial microcapsules, characterized in that include: 1) Mix the melted phase change material and the antibacterial agent, cool them, and obtain the core material; 2) Dissolve sodium alginate in a 5-15wt% isopropanol-water solution, add the core material, heat to melt the phase change material, add the emulsifier hydrophobic nano calcium carbonate, and stir evenly; The solid-liquid ratio of sodium alginate to isopropanol-water solution is 1.5-3g / 100mL; the solid-liquid ratio of hydrophobic nano-calcium carbonate to isopropanol-water solution is 0.8-1g / 100mL; the solid-liquid ratio of core material to isopropanol-water solution is 4-6g / 100mL; 3) dropping the acid solution into the product of 2), adding dopamine hydrochloride and the catalyst at the same time, heating and stirring; the solid-to-liquid ratio of dopamine hydrochloride to the isopropanol-water solution in 2) is 0.08-0.12 g / 100 mL; 4) pouring the product of 3) into water and filtering to obtain synergistic antibacterial microcapsules with an average particle size of 30-100 microns; 5) preparing the synergistic antimicrobial microcapsules into a solution as component b for post-immersion of wood; 6) Prepare chitosan solution as component a for pre-soaking wood.
2. The preparation method according to claim 1, characterized in that: 1), the mass ratio of the phase change material to the antibacterial agent is (2500-7500):(5-15).
3. The preparation method according to claim 1, characterized in that: 1), the phase change material is paraffin with a melting point of 48-50°C; The antibacterial agent is amoxicillin.
4. The preparation method according to claim 2, characterized in that: 2) In The heating and melting temperature is 55-65°C; The stirring speed is 500-1000 rpm, and the stirring time is 1-5 h.
5. The preparation method according to claim 1, characterized in that: 3) In The acid solution is an aqueous solution of acetic acid with a concentration of 0.5-1.5M; The volume ratio of the acid solution to the isopropanol-water solution in 2) is (5-15):
100.
6. The preparation method according to claim 1, characterized in that: 3), wherein the catalyst is ammonium persulfate.
7. The preparation method according to claim 1, characterized in that: 3), the heating and stirring temperature is 55-65°C, the stirring speed is 200-600 rpm, and the time is 1-5h.
8. A wood antibacterial and anticorrosive coating, characterized in that: Comprising independent components a and b; wherein: Component a is a chitosan solution, which is used to pre-soak the wood; Component b is a solution containing the synergistic antibacterial microcapsules obtained according to the preparation method according to any one of claims 1 to 7, and is used for post-immersion of wood.
9. The wood antibacterial and anticorrosive coating according to claim 8, characterized in that: The content of chitosan in the component a is 1-3wt%.
10. The wood antibacterial and anticorrosive coating according to claim 8, characterized in that: The content of the synergistic antibacterial microcapsules in component b is 1-3wt%.